FORMATION OF QUANTITATIVE REPRESENTATIONS IN PRESCHOOL CHILDREN IN THE PROCESS OF MATHEMATICAL GAMES - Kurbon, Ostanov; Jasur, Kadirov; Jasur, Kadirov; O’tkir, Achilov; O’lmas, Totliyev (International Journal of Psychosocial Rehabilitation, 2020)
: the article analyzes various approaches to the content and methods of forming quantitative representations in preschool children, as well as the technology of forming the ability to group objects (2-6 years), the formation of ideas about the multiplicity and unity of objects (from 3 to 5 years), the formation of the ability to distinguish 1 and a lot of objects in the environment (from 3 to 4 years), the formation of the ability to compare 2 groups of objects by quantity, by establishing a one-to-one correspondence (from 3 to 6 years) the content of the training methodology eniya counting of objects (4 - 6 years), teaching methods ordinal account (4 - 6 years), and provides recommendations for their implementation in practice.